2016
DOI: 10.1080/17470919.2016.1247012
|View full text |Cite
|
Sign up to set email alerts
|

As tears go by: Baby tears trigger more brain activity than adult tears in nulliparous women

Abstract: The current functional magnetic resonance imaging study examines brain activity during the perception of infant and adult tears. Infant tears evoke stronger responses in the visual cortex than adult tears, indicating that infant tears are highly salient. In addition, our study shows that infant tears uniquely activate somatosensory pain regions, which could stimulate actions directed at the elimination of the source of pain. Shedding tears may be a strong means to elicit the parent's sharing of the infant's fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…When babies cry they convey a message to the parents that they are not comfortable and that their needs are to be met, be these physiological or emotional [17]. Since a baby's crying has a high emotional content the parents nd it di cult to ignore [18] [19]. Normally this works ne because it compels the parents to tend to the baby's needs, and once this has been achieved the crying and fussing stops.…”
Section: Discussionmentioning
confidence: 99%
“…When babies cry they convey a message to the parents that they are not comfortable and that their needs are to be met, be these physiological or emotional [17]. Since a baby's crying has a high emotional content the parents nd it di cult to ignore [18] [19]. Normally this works ne because it compels the parents to tend to the baby's needs, and once this has been achieved the crying and fussing stops.…”
Section: Discussionmentioning
confidence: 99%
“…When babies cry they convey a message to the parents that they are not comfortable and that their needs are to be met, be these physiological or emotional [17]. Since a baby's crying has a high emotional impact the parents nd it di cult to ignore [18] [19]. Normally this is ne because it compels the parents to tend to the baby's needs, and once these have been met, the crying and fussing stops.…”
Section: Discussionmentioning
confidence: 99%
“…Using this task, a prior study demonstrated that participants are faster in avoiding (vs approaching) sad infants faces but not happy ones (De Carli, Riem, & Parolin, 2017). This tendency to avoid sad infants may be related to the fact that infant distress signals trigger feelings of shared distress in adults (Riem, van IJzendoorn, De Carli, Vingerhoets, & Bakermans-Kranenburg, 2017a), possibly through neural simulation mechanisms, which motivate an avoidant response in order to reduce negative emotionality.…”
Section: Introductionmentioning
confidence: 94%